2011
DOI: 10.1007/s11427-011-4215-5
|View full text |Cite
|
Sign up to set email alerts
|

The internalization pathway, metabolic fate and biological effect of superparamagnetic iron oxide nanoparticles in the macrophage-like RAW264.7 cell

Abstract: The potential applications of superparamagnetic iron oxide nanoparticles (SPIONs) in several nanomedical fields have attracted intense interest based on the cell-nano interaction. However, the mechanisms underlying cell uptake, the intracellular trail, final fate and the biological effects of SPIONs have not yet been clearly elucidated. Here, we showed that multiple endocytic pathways were involved in the internalization process of SPIONs in the RAW264.7 macrophage. The internalized SPIONs were biocompatible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 50 publications
9
83
3
1
Order By: Relevance
“…5). Gu et al reported that internalized USPIO in mouse macrophages was degraded in lysosomes, and free iron was released into intracellular iron pools (23). Fpn1 is known to have an important role in the export of iron from cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…5). Gu et al reported that internalized USPIO in mouse macrophages was degraded in lysosomes, and free iron was released into intracellular iron pools (23). Fpn1 is known to have an important role in the export of iron from cells (19).…”
Section: Discussionmentioning
confidence: 99%
“…These results confirmed that several endocytic uptake mechanisms worked cooperatively for uptake of SPIONs by macrophage-like RAW264.7 cells. 64 However, in another study by Yang et al, ferucarbotran, a clinically approved SPIO-coated carboxydextran with a mean diameter range of 45-60 nm, was found to be internalized in macrophage-like RAW264.7 cells via clathrin-dependent endocytosis. 65 It seems that there is a correlation between SPION factors (size, surface charge, and surface coating) and endocytotic pathways, that needs to be explored in more detail.…”
Section: Internalization and Biodistribution In Different Cellsmentioning
confidence: 97%
“…Thirdly, some of the internalized SPIONs may potentially be exocytosed out of RAW264.7 cells, although direct evidence for this proposed mechanism is lacking. 64 Levy et al conducted a long-term (3-month) in vivo biotransformation study of 8 nm SPIONs coated with hydrophilic glucose derivatives following intravenous administration in mice. Using ferromagnetic resonance and superconducting quantum interference device measurements, they supported the view of continuous biotransformation of injected magnetic nanoparticles into iron storage species within intracellular lyzosomes.…”
Section: Metabolismmentioning
confidence: 99%
“…Several previous studies examined the effects of DMSA-MNP on different cell types, and showed little reduction in cell viability [11,16,40]. These studies used low MNP doses, however, or incubation times too short to permit analysis of all possible toxic effects of iron oxide nanoparticles.…”
Section: In Vitro Dmsa-mnp Cytotoxicitymentioning
confidence: 99%